Mechanical Properties of Resistance Spot Welded Components of High Strength Austenitic Stainless Steel. Issue 6 (June 2016) - Liu, Wei; Fan, Hailong; Guo, Xiangzhong; Huang, Zhihong; Han, Xiaohui
Abstract : Resistance multi-spot welding (MSW) in column, triangle and tetragonal symmetry arrangements was prepared using cold-rolled 301L high-strength sheets, and their static and fatigue properties were investigated. The effects of spot welds on the fracture strengths and fatigue limits were discussed. The results show that the static strengths can be estimated using an inherent linear relationship formula of the load versus the welding area. It was based on the 28%–33% volume fraction of α′ martensite induced at the interfacial spot weld fracture because of the failure deformation. The fatigue limits of the MSW nonlinearly increase with the number of spot welds. The arrangement of spot welds in the MSW significantly affects the average fatigue limit of each spot weld; its 26% maximum reduction occurred in the triangle, and the interaction stress between spot welds led to its 18% reduction in the tetragonal symmetry. The calculated fatigue stress of all MSW loadings with their mean fatigue limits was 230–270 MPa.